Sentidos de Atendimento Educacional Especializado produzidos por professoras de salas de recursos multifuncionais de um município gaúcho da região metropolitana - León, Silvana Corrêa Vieira de (Universidade do Vale do Rio dos Sinos, 2023)
The present study, part of the Graduate Program in Applied Linguistics at Unisinos, in the Language and School Practices research line, aims to identify the meanings of Specialized Educational Assistance (AEE) that emerge from the discursive productions of teachers working in Multifunctional Resource Rooms (SRM) in a municipality in the metropolitan region of Porto Alegre and the effects produced in pedagogical relations in the context of Inclusive Education. The thesis analyzes aspects involving the field of language in Special and Inclusive Education, adopting Vygotsky's Sociocultural Theory (2008) as a base, emphasizing the role of language, interaction, collaborative mediation, and the socio-historical process in individual development. From an inclusive perspective, Special Education is considered integrated into the regular school’s pedagogical proposal. The study adopts a qualitative-interpretative approach, using narrative analysis and considering linguisticinteractional and discursive aspects, based on the studies of Moita Lopes (2006), Bastos and Biar (2005, 2015). Data were generated through semi-structured online interviews, due to the Covid-19 pandemic, and a face-to-face formative meeting in June 2022. The results indicate movements in teachers' practices, especially in collaboration with common room teachers, showing a meaning for AEE that goes beyond individualized work in SRMs. Nationally, movements and tensions in the field of Special Education highlight the importance of AEE and the meanings produced by teachers in this context. The National Policy on Special Education from the perspective of Inclusive Education (PNEEPEI) (BRASIL, 2008) and the CNE/CEB Resolution 4/2009 guide the organization and functioning of AEE, specifically in SRMs. AEE is seen as a space for re-signifying pedagogical practices in the inclusive context. The discursive productions of teachers reveal actions that promote possible shifts in meanings for AEE in the school setting, requiring articulation with school management. The importance of listening to AEE teachers is reiterated to strengthen their teaching protagonism and tension shifts in meanings regarding the attributions of this professional. The thesis defends the potential contribution to the training of AEE teachers in the municipal network, from the understanding of the role of language in inclusive practices in schools, SRMs, and interaction with the entire school community.

El presente estudio, insertado en el Programa de Posgrado en Lingüística Aplicada de Unisinos, línea de investigación Lenguaje y Prácticas Escolares, tiene como objetivo identificar los sentidos de AEE que emergen de las producciones discursivas de las profesoras que actúan en Salas de Recursos Multifuncionales (SRM) en un municipio de la región metropolitana de Porto Alegre y los efectos producidos en las relaciones pedagógicas en el contexto de la Educación Inclusiva. La tesis analiza aspectos que involucran el campo del lenguaje en la Educación Especial e Inclusiva, adoptando la Teoría Sociocultural de Vygotsky (2008) como base, enfatizando el papel del lenguaje, la interacción, la mediación colaborativa y el proceso histórico-social en el desarrollo individual. Desde una perspectiva inclusiva, se considera la Educación Especial integrada a la propuesta pedagógica de la escuela regular. El estudio adopta un enfoque cualitativo-interpretativo, utilizando el análisis de narrativa y considerando aspectos lingüístico-interaccionales y discursivos, basándose en los estudios de Moita Lopes (2006), Bastos y Biar (2005, 2015). Los datos se generaron a través de entrevistas semiestructuradas en línea, debido a la pandemia de Covid-19, y un encuentro formativo presencial en junio de 2022. Los resultados indican movimientos en las prácticas de las profesoras, especialmente en colaboración con los profesores de la sala común, evidenciando un sentido para el AEE que va más allá del trabajo individualizado en las SRM. A nivel nacional, los movimientos y tensiones en el campo de la Educación Especial destacan la importancia del AEE y los sentidos producidos por los profesores en este contexto. La Política Nacional de Educación Especial en la perspectiva de la Educación Inclusiva (PNEEPEI) (BRASIL, 2008) y la Resolución 4/2009 del CNE/CEB orientan las directrices para la organización y funcionamiento del AEE, específicamente en las SRM. El AEE se considera un espacio de resignificación de prácticas pedagógicas en el contexto inclusivo. Las producciones discursivas de las profesoras revelan acciones que promueven posibles desplazamientos de sentidos para el AEE en el entorno escolar, necesitando articulación con la gestión escolar. Se reitera la importancia de momentos de escucha a las profesoras del AEE para fortalecer el protagonismo docente y tensionar los desplazamientos de sentidos sobre las atribuciones de este profesional. La tesis defiende la contribución potencial para la formación de profesores del AEE de la red municipal, a partir de la comprensión del papel del lenguaje en las prácticas inclusivas en las escuelas, SRM y en la interacción con toda la comunidad escolar.
Keywords: Atendimento educacional especializado; Formação docente; Interação; Linguagem; Specialized education service; Teacher training; Interaction; Language; Atención educativa especializada; Formación docente; Interacción; Lenguaje; ACCNPQ::Linguística, Letras e Artes::Linguística Aplicada